The refugee drama in Syria, Turkey, and Greece: Why a comprehensive approach is needed - Sinem Adar; Steffen Angenendt; Muriel Asseburg; Raphael Bossong; David Kipp (Stiftung Wissenschaft und Politik (SWP), 2020)
The plight of refugees in the Syrian province of Idlib, on the Greek islands, and on the EU's external borders has worsened dramatically over the last few months. Once more, the European Union (EU) is split on questions of asylum and migration, and it portrays limited capacity to act in issues of foreign and security policy. What options does the EU have to address the deteriorating situation? This question has become even more pressing due to the spread of Covid-19. The EU-Turkey statement of 2016 has strengthened cooperation with Ankara on humanitarian aid and border controls, but it also has major weaknesses. A comprehensive approach is needed. The EU should prioritise providing new financial resources for Turkey that should be complemented by scaling-up assistance to Greece as well as to Syria's neighbours. In addition, the Europeans should support the creation of a safe zone in northern Idlib.
Keywords: 320